PROPERTIES OF ACTIVATED CARBON PREPARED FROM RICE HUSK WITH CHEMICAL ACTIVATION - Daffalla, S.B. (2010)
Adsorption process is gaining interest as one of the effective processes of advanced wastewater treatment for treatment of industrial effluent containing toxic materials. Among various water pollutants, phenol and its derivatives are the most toxic because they are carcinogenic in nature. Although commercial activated carbon is a preferred adsorbent for phenol removal, its widespread use is restricted due to the high cost. The objective of this study was to develop activated carbon from rice husk by chemical activation with zinc chloride (ZnCl2) and phosphoric acid (H3PO4) under different activation atmospheres. Experiments were carried out at different chemical ratios of activating agent and precursor. The carbonization temperature which had significant effect on the pore structure of carbon was also varied. It was found that the carbon yield using ZnCl2 and H3PO4 as the activating agent increased with impregnation ratio. The physical and surface properties of the developed adsorbents were characterized using FTIR and SEM. The results showed that, when rice husks activated with H3PO4 and ZnCL2, the band at 1080 cm-1 and 862-476 cm-1 decreased, indicating the removal of ash in carbons. For both activation procedures, the intensity of C≡C, C=C, CH2 and CO bands decreases as the activation temperature increases, indicating that the proportion of carbon content increases at high temperatures. The effective of these adsorbents were tested via separation of artificial wastewater containing phenol. This is evaluated by varying the adsorbent doses. Results showed that efficiency up to 90% could be achieved with 0.5 g ZnCl2 activated carbon at 500oC and 600oC activating temperature. But with this condition by 0.1 g adsorbent, the removal efficiency between 80-85 % at (500oC) and 69-74 % at (600oC).On the other hand , efficiency achieved with H3PO4 activated carbon more less than ZnCL2 activated carbon, about 45-48% (500oC) and 41-45% (600oC) achieved with 0.1g and 48-56% at (500oC) and43-51% at (600oC) with 0.5 g H3PO4 activated carbon . The kinetics of phenol adsorption on both ZnCL2 and H3PO4 activated carbons were found to follow the pseudo-second-order kinetic model. Analysis of FTIR shows that the –OH, C-H, C≡C, C=O, C=C, C-C and C-O groups contribute to the adsorption of phenol onto the surface of adsorbent.